Differences in thigh muscularity and dynamic torque between junior and senior soccer players - Hoshikawa, Y.; Iida, T.; Muramatsu, M.; Nakajima, Y.; Fukunaga, T.; Kanehisa, H. (Journal of Sports Sciences, 2009)
The aim of the present study was to examine differences in thigh muscularity and dynamic torque between elite junior (15.7 ± 0.2 years) and senior (22.6 ± 2.4 years) soccer players. Cross-sectional areas of the total muscle compartment, quadriceps femoris, and hamstrings + adductors were determined using magnetic resonance imaging. Knee extension and flexion torque were also measured at 1.05 and 3.14 rad · s-1. Neither junior nor senior players showed significant differences in cross-sectional area or torque between the dominant and non-dominant leg. The quadriceps femoris and hamstrings + adductors were significantly greater in the senior than junior players at all thigh-slice sites. The percentage of quadriceps femoris to total muscle compartment was significantly higher in the junior than the senior players, and the corresponding value of hamstrings + adductors was significant in the reverse direction. The senior players showed greater torque than the juniors regardless of motion and velocity, even in terms of torque relative to the product of the cross-sectional area and height. The present results indicate that (1) senior players are characterized by the predominant development of hamstrings and adductors and a higher dynamic torque relative to muscle size, and (2) elite soccer players did not show asymmetry in terms of the muscularity or dynamic torque of the thigh muscles irrespective of age.